Implementation of the INTERGROWTH‐21st Project in the United States. (11th July 2013) - Dighe, MK; Frederick, IO; Andersen, HF; Gravett, MG; Abbott, SE; Carter, AA; Algren, H; Rocco, DA; Waller, SA; Sorensen, TK; Enquobahrie, D; Blakey, I; et al.
Abstract : The North American site in the INTERGROWTH‐21 st Project was North Seattle, Washington State, USA. The majority of the data were collected from within Seattle City, which has approximately 12 300 births per year. The sample for the Newborn Cross‐Sectional Study (NCSS) was drawn from two hospitals (Swedish Medical Center and the University of Washington) covering almost 80% of deliveries within the target population. The Fetal Growth Longitudinal Study (FGLS) sample was recruited from several antenatal clinics serving the University of Washington Medical Center and Providence Everett Medical Center. Special activities to encourage participation and raise awareness of the studies included furnishing the recruitment sites with fliers designed by the Project Coordinating Unit, and presenting the studies to clinical staff to encourage providers to refer appropriate patients. One of the major challenges at this site was the low recruitment rate in the early phase of the FGLS because of the high rates of smoking, maternal age >35 years and body mass index >30 years. This was remedied by the inclusion of other ancillary clinics, as well as increased advertising among the general public.